PENGUKURAN, EVALUASI DAN ASESMEN SERTA TUJUAN DAN FUNGSI EVALUASI DALAM PEMBELAJARAN PAI - Ikbal, Ahmad; Andrianto, Andrianto; Suryaningrum, Evi; Muniroh, Badriyatul; Gusnita, Fitri; Julhadi, Julhadi (Dharmas Education Journal (DE_Journal), 2025)
Improving the quality of the assessment system is one of the initiatives aimed at improving educational standards. A strong learning framework will produce high-quality education, encourage educators to develop effective teaching strategies, and inspire students to engage in their learning more effectively. Measurement, assessment, assessment and evaluation each have a different scope and focus. The method in this research is a literature study which is used to analyze literature relevant to the research topic. This research does this by analyzing literature related to the concepts of measurement, evaluation and assessment in Islamic Religious Education. The scope of assessment is shorter and is usually only limited to one element, such as student achievement, student activity and so on. In addition, assessments are carried out and used by individuals involved or part of the system in question. A broader evaluation covers all system components, such as the education system, curriculum and learning. This can be done by internal and external evaluation. In essence, student learning outcomes are categorized into three areas: cognitive, affective, and psychomotor. It is hoped that teachers can develop this area well in every lesson. Evaluation activities were carried out to determine the development of these three fields.